Skill mix and patient outcomes: A multi-country analysis of heart disease and breast cancer patients. Issue 10 (October 2020) - Kopasker, Daniel; Islam, M. Kamrul; Gibson, Jonathan; Lau, Yiu-Shing; Sutton, Matt; Askildsen, Jan Erik; Bond, Christine; Elliott, Robert; ,
Highlights: Variations in skill mix are associated with positive and adverse patient outcomes. A task component-based measure of skill mix is used. Novel skill mix measure is specific to a care pathway. Influence of skill mix on outcomes varies across pathways. Some evidence of consistent effect across health systems within pathway. Abstract: Policymakers are becoming aware that increasing the size of the healthcare workforce is no longer the most viable way to address the increasing demand for healthcare. Consequently, a focus of recent healthcare workforce reform has been extending existing roles and creating new roles for health professionals. However, little is known of the influence on outcomes from this variation in labour inputs within hospital production functions. Using a unique combination of primary and administrative data, this paper provides evidence of associations between the composition of care delivery teams and patient outcomes. The primary data enabled the construction of a task component-based measure of skill mix. This novel measure of skill mix has the advantage of capturing how workforce planning can restructure the relative input of nurses or physicians into task components while keeping the overall level of staff fixed. The analysis focuses on specific care pathways and individual hospitals, thus controlling for an under-investigated source of heterogeneity. Additionally, stratifying by country (England, Scotland, and Norway) enabled analysis of skill mix within different health systems. We provide evidence that variations in labour inputs within the breast cancer and heart disease care pathways are associated with both positive and adverse outcomes. The results illustrate the scope for substitution of task components within care pathways as a potential method of healthcare reform.